Principal’s Strategy in Developing Teacher’s Pedagogic Competencies in the Distance Learning - Sinta Diah Ayu Wandani; Mohamad Ali; Muh. Nur Rochim Maksum; Muhammad Badat Alauddin (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2022)
The teachers’ pedagogic competence significantly influences the students’ learning process and outcomes. Due to the Distance Learning policy, the principal as a manager of the school is expected to have the right strategy to develop the ability of teachers professionally to continue to provide quality educational services. This study aims to report the response of teachers to distance learning policy and strategies of the principals of SMA Muhammadiyah PK in Solo Raya in developing teachers’ pedagogic competencies. This study is qualitative research that employed the phenomenological method. The validity of the data was obtained using technical triangulation and source triangulation as well as data analysis by reducing data, presenting data, and drawing conclusions. This study found the followings: 1) The teachers felt hard to adjust at the beginning; 2) The teachers continued to look for and apply appropriate learning methods; 3) The teachers had a little difficulty engaging students during learning; 4) The teachers needed to adjust and needed guidance to understand and prepare lesson plans according to the emergency curriculum. Furthermore, in developing teacher pedagogic competence, the principal supervised learning and conducted several training programs accompanied by practice, motivation, and advice. Keywords:  Principal’s Strategy, Pedagogic Competence, Distance Learning